ANALISIS DEIKSIS PADA FILM “LOSMEN BU BROTO” - Tanjung, Yessi; Anggraini Ginting, Dinda; Sabrina Barus, Elsa; Lubis, Fitriani (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Deixis is a word or phrase whose reference is not fixed. This research examines the various kinds of diexistence contained in each story conveyed by each character in the film "Losmen Bu Broto" by Ifa Isfansyah and Eddie Cahyono. This study uses a qualitative descriptive research method. The data in this study were collected using the listening method, namely by recording and noting techniques. Data analysis illustrates that the film directed by Ifa Isfansyah and Eddie Cahyono with the title "Losmen Bu Broto" has a deixis of persona, time, place, social, and discourse. The results of the study show that there is digression in the film "Bu Broto's Inn". In this study, 72 charm deixis were found, which were divided into the first charm deixis (I, I, we, and us), the second charm deixis (you, you, and you), and the third charm (he and they). Then, the researcher found 18 place deixis, 18 time deixis, 11 social deixis, and 15 discourse deixis. Based on the research results, it can be concluded that there are 134 deixis in the film "Losmen Bu Broto" by Ifa Isfansyah and Eddie Cahyono.